Suasana Mendung di Cempaka Sari - Noor Azizan Rahman Paiman, (Wacana Seni Journal of Arts Discourse, 2020)
This work entitled “Suasana Mendung di Cempaka Sari” in terms of ideas is held through environmental experience encountered by the artist since residing in Perak (from 2001 until now). The artist lives in Seri Manjung district and works at Universiti Teknologi MARA (UiTM) Perak Branch, Seri Iskandar (in Bota sub-district). Hence the daily travel distance of the artist goes back and forth from home to work and vice versa is about 100 kilometres. Through “daily activities” back and forth, the artist indirectly has been served with various shapes and visual elements pertaining to “social products” that are having “potential” to be questioned such as politics, economics, culture, religion, or environment in supporting the formation of his ideas for designing artwork.